I IMPLEMENTASI SMART EDUCATION SEBAGAI BAGIAN DARI PENERAPAN SMART CITY DI KOTA BATAM - Saut Pintubipar Saragih (Universitas Putera Batam, 2018)
Smart education is an education system that has used the smart concept in the implementation of education. Smart Education is illustrated by the main things implemented by universities, namely adaptive learning, portfolio learning, collaborative technologies and learning resources, administrative processes that have been computerized or using interconnected computer networks and monitoring and reporting, availability of more complete information, accurate and detailed, the university must also provide online learning resources that can be accessed by all students and lecturers through computer devices or mobile devices through a computer network, internet, intranet or a combination of both. In Batam, not all universities apply the concept of smart education, but based on existing data that all universities in Batam have implemented technologies such as academic information systems. universities in the city of Batam have not been able to apply the concept of smart education where difficult system integration is a problem faced. In this study found also the resistance of the manager to survive with the current system on the grounds that there is no urgency than the implementation of smart education.